The Lived Experience of Pain and Depression Symptoms during Pregnancy. Issue 4 (July 2021) - Vignato, Julie; Beck, Cheryl Tatano; Conley, Virginia; Inman, Michaela; Patsais, Micayla; Segre, Lisa S.
Abstract: Background: Depressive symptoms and pain are prevalent during pregnancy. Untreated pain and depressive symptoms occurring together may have a negative effect on maternal and newborn outcomes, yet little is known about women's experiences with pain and depressive symptoms during pregnancy. The purpose of this study is to describe the lived experience of depressive symptoms and pain occurring in women during the third trimester of pregnancy. Methods: A descriptive phenomenological study was conducted. Women during postpartum were recruited from a previous cross-sectional study of women in their third trimester that evaluated the relationship between pain, depression, and quality of life. Twenty-four women entered their responses into an online secure research Web site. These data were analyzed using Colaizzi's method of descriptive phenomenological analysis. Results: Four themes that described the essence of women's experiences with both pain and depressive symptoms were identified. They were pregnancy: feeling minimized, unheard and overwhelmed; attempting or trying but not treated: living with pain and pain interference; pain, sleep loss, and suffering; and pain and depressive symptoms: helpless, hopeless, and suffering . Clinical Implications: If a woman presents with pain, additional nursing assessments of her sleep and emotional state may be needed. Likewise, a positive depression symptom screening suggests the need for a more in-depth exploration of pain, pain interference, poor sleep, and mental health symptoms. Because the women perceive their pregnancy as minimized, nurses may need to assist in setting realistic expectations and encouraging social support. Nurses listening to women describing these conditions may be essential in promoting the women's wellbeing. Abstract : Depressive symptoms and pain are prevalent during pregnancy. Untreated pain and depressive symptoms occurring together may have a negative effect on maternal and newborn outcomes, yet little is known about women's experiences with pain and depressive symptoms during pregnancy. In this study, the lived experience of depressive symptoms and pain occurring in women during the third trimester of pregnancy is explored.